INVESTASI DAERAH DAN E-GOVERNMENT SERTA IMPLIKASINYA TERHADAP KEMANDIRIAN DAERAH - Ibnu Hamzami Ulfi (Bina Ekonomi, 2021)
Regional independence is still homework for most local governments, as can be seen from small contributions of most local governments. This study aims to examine empirically the effect of regional investment and e-government on regional independence with samples of 33 provinces in Indonesia in 2019. Regional investment is measured by the amount of long-term investment in the balance sheet, while e-government is measured by the results of the SPBE evaluation. Data processing is using IBM SPSS 26 software with multiple regression analysis methods with qualified requirements in the classical assumption test. Based on the calculation of regional investment, there is a significance value of 0.015. The value is <0.05 so it can be concluded that regional investment has significant effects on regional independency. These results can also be interpreted that funds which are invested by local governments to local companies can contribute in increasing the local income. However, different results were obtained by the e-government variable which produced a significant value of 0.080 and the value is > 0.05, so it can be concluded that e-government has no significant effect on regional independency. These results of study are expected to provide recommendations to local governments to invest continuously in regional companies, especially to those that are productive in generating profits, fixing and improving the electronic-based public services, especially concerning in increasing local income as an important element in regional independence.